Use of Hepatocellular Carcinoma Surveillance in Patients With Cirrhosis: A Systematic Review and Meta‐Analysis. Issue 2 (20th November 2020) - Wolf, Erin; Rich, Nicole E.; Marrero, Jorge A.; Parikh, Neehar D.; Singal, Amit G.
Abstract : Background and Aims: Hepatocellular carcinoma (HCC) surveillance is associated with early tumor detection and improved survival; however, it is often underused in clinical practice. We aimed to characterize surveillance use among patients with cirrhosis and the efficacy of interventions to increase surveillance. Approach and Results: We performed a systematic literature review using the MEDLINE database from January 2010 through August 2018 to identify cohort studies evaluating HCC surveillance receipt or interventions to increase surveillance in patients with cirrhosis. A pooled estimate for surveillance receipt with 95% confidence intervals was calculated. Correlates of surveillance use were defined from each study and prespecified subgroup analyses. Twenty‐nine studies, with a total of 118, 799 patients, met inclusion criteria, with a pooled estimate for surveillance use of 24.0% (95% confidence interval, 18.4‐30.1). In subgroup analyses, the highest surveillance receipt was reported in studies with patients enrolled from subspecialty gastroenterology/hepatology clinics and lowest in studies characterizing surveillance in population‐based cohorts (73.7% versus 8.8%, P < 0.001). Commonly reported correlates of surveillance included higher receipt among patients followed by subspecialists and lower receipt among those with alcohol‐associated or nonalcoholic steatohepatitis (NASH)–related cirrhosis. All eight studies (n = 5, 229) evaluating interventions including patient/provider education, inreach (e.g., reminder and recall systems), and population health outreach strategies reported significant increases (range 9.4%‐63.6%) in surveillance receipt. Conclusions: HCC surveillance remains underused in clinical practice, particularly among patients with alcohol‐associated or NASH‐related cirrhosis and those not followed in subspecialty gastroenterology clinics. Interventions such as provider education, inreach including reminder systems, and population health outreach efforts can significantly increase HCC surveillance.